State Capture of the Post-Socialist State: Challenges to European Integration - Nonchev, Andrei (Research Papers, 2019)
The paper discusses alternative trajectories of post-socialist societal transformations, with an emphasis on a specific state of society designated as "state capture". It presents a theoretical model of the interaction between public institutions, power networks and their rational political and economic strategies/actions to capture the state. This model interprets the state capture not as an anonymous actorless process, but as a rational pursuit of specific strategies for acquisition, concentration and preservation of political and economic power and extraction of economic benefits/rents. The implementation of these strategies involves the formation and operation of the politico-economic power networks that seek to control key public legislative, executive and judiciary institutions. These processes are not random and sporadic deviations but have a systematic nature and significant political, economic and social consequences. They pose a serious challenge to the EU integration of the post-socialist countries.
Keywords: Politico-economic power networks; Rule of law; State capture; Corruption; European integration